2006
DOI: 10.1002/cncr.22292
|View full text |Cite
|
Sign up to set email alerts
|

The role of FDG‐PET/CT in suspected recurrence of breast cancer

Abstract: BACKGROUND. Early diagnosis of recurrent breast cancer is crucial to selection of the most appropriate therapy. The current study evaluated the role of FDG‐PET/CT in the assessment of suspected recurrent breast cancer in patients who presented with elevated serum tumor markers. METHODS. Forty‐seven consecutive FDG‐PET/CT studies of 46 women (aged 32–79 years; mean, 59.9 years) with a history of breast cancer presented with elevated serum tumor markers 1–21 years (mean = 6.2 years) after their initial diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 13 publications
7
120
0
5
Order By: Relevance
“…Recently, several studies pointed out that staging with 18 F-FDG PET/CT might be of value not only in patients with locally advanced disease but also in "intermediate-risk" patients (13-21)-that is, patients with clinical stage IIB disease (T2N1/T3N0) or higher-with significant diagnostic yield and prognostic information (18,19). PET/CT has also shown good performance in restaging for breast cancer patients (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).This review assesses the advantages and limits of 18 F-FDG PET/CT in initial staging and restaging for breast cancer patients. …”
mentioning
confidence: 99%
“…Recently, several studies pointed out that staging with 18 F-FDG PET/CT might be of value not only in patients with locally advanced disease but also in "intermediate-risk" patients (13-21)-that is, patients with clinical stage IIB disease (T2N1/T3N0) or higher-with significant diagnostic yield and prognostic information (18,19). PET/CT has also shown good performance in restaging for breast cancer patients (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).This review assesses the advantages and limits of 18 F-FDG PET/CT in initial staging and restaging for breast cancer patients. …”
mentioning
confidence: 99%
“…18 F-FDG PET/CT accurately stages various types of tumors (9)(10)(11). In addition, whole-body 18 F-FDG PET/CT is beneficial for staging breast cancer (12)(13)(14) and for monitoring therapy in breast cancer patients (15). However, 18 F-FDG PET/CT has predominantly been used to detect distant metastases in breast cancer patients.…”
mentioning
confidence: 99%
“…Preliminary studies on small cohorts of patients have shown a correlation between early reduction of tumor FDG uptake and clinical response after completion of neo-adjuvant chemotherapy. [8] The patients included in this study were subdivided into three groups according to the referring cause for PET/CT post-operative follow up.…”
Section: Discussionmentioning
confidence: 99%